(untitled) (Journal of Partial Differential Equations, 2020)
In this paper, we studied and completely solved the problem on the anornal uniqueness of the equation system u_x + ixu_y = -ix&sup2&#934v_y v_z + ixu_y = -ix&sup2&#934v_y The so-called anormal uniqueness means as follows: suppose all order derivatives of u vanish on &#8706D, one can draw the conclusions of u = 0(D), v &#8801 const(D).